2015
DOI: 10.1021/acs.langmuir.5b00306
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Surface-Modified Silica Nanoparticles to the Interface of Melt Poly(lactic acid) and Supercritical Carbon Dioxide

Abstract: With the purpose of fabricating polymer nanocomposite foams and preventing coalescence in foaming processes, the interfacial tension of poly (lactic acid) (PLA) -silica composites is investigated in this work. Synthesized silica nanoparticles (SNs) with a CO 2 -philic surface modification are used as the dispersed nanoparticles. Interfacial tension is a key parameter in processing of polymer foams since it directly affects the final foam properties, such as cell size and cell density. Interfacial tension of si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 68 publications
(154 reference statements)
0
17
0
Order By: Relevance
“…Some of the advantages of using the drop shape method for measuring the interfacial tension include: the ability to use a small volume of liquid; its applicability to liquid‐vapour and liquid‐liquid interfaces; and broad ranges of temperature and pressure. A detailed procedure of this method can be found elsewhere . In the interfacial tension experiments, a pendant drop of a suitable size was formed at the end of a stainless‐steel holder that was connected to a 500 μL syringe (Gastight, Hamilton Co. Model 1750 TLLX) with a blunt needle of diameter 1.8 mm.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the advantages of using the drop shape method for measuring the interfacial tension include: the ability to use a small volume of liquid; its applicability to liquid‐vapour and liquid‐liquid interfaces; and broad ranges of temperature and pressure. A detailed procedure of this method can be found elsewhere . In the interfacial tension experiments, a pendant drop of a suitable size was formed at the end of a stainless‐steel holder that was connected to a 500 μL syringe (Gastight, Hamilton Co. Model 1750 TLLX) with a blunt needle of diameter 1.8 mm.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The dynamic oil‐water interfacial tension was measured for varying starch nanoparticle concentrations in the aqueous phase. The cuvette containing the drop was housed in an optical viewing cell through which the pendant drop was monitored during the experiment. A magnified image of the pendant drop was acquired by a charged coupled device (CCD) monochrome camera and a microscope.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Thus, the hydrolytic degradation ability of PLLA/silica composites was accelerated in the presence of higher loadings of silica in the polymer matrix. The impact of silica nanoparticles on the interfacial tension between PLA and supercritical CO2 at high temperature and high pressures was examined by Sarikhani and coworkers [92]. The addition of a low loading of silica (less than 2 wt.%) led to reducing the interfacial tension, while the interfacial tension tended to increase when the silica content was larger than 2 wt.%, which was linked to the fact that higher levels of silica originated attractive lateral capillary forces due to the perturbation of the PLA-CO2 interface by particles.…”
Section: Biodegradbility and Other Propertiesmentioning
confidence: 99%
“…Nanoparticles can be used to improve PLA foamability through the improvement in crystallization, melt strength, and reduction of interfacial tension of the PLA system. It has been shown that both carbon dioxide (CO 2 ) dissolution [20,21] and the addition of nanoparticles [22] can reduce the interfacial tension of PLA e CO 2 mixtures. In addition, nanoparticles can serve as nucleating agents in the nucleation step of foaming [23,24].…”
Section: Introductionmentioning
confidence: 99%